THE CRITICAL SUCCESS FACTORS OF HIV/AIDS PREVENTION COLLABORATION IN DKI JAKARTA - Jaya, I Gede Sumitra; Retnandari, Nunuk Dwi (Dialogue : Jurnal Ilmu Administrasi Publik, 2024)
The purpose of this research is to comprehend and elucidate the collaborative governance phenomenon in the HIV/AIDS prevention program in DKI Jakarta, as well as to examine and evaluate the factors contributing to the collaboration’s success among the various stakeholders involved. The research employed a qualitative method with a descriptive analysis approach, gathering data through focus group discussions and in-depth interviews. The research discovers that the factors influencing the collaboration’s success include networked structure, commitment to a common purpose, trust among participants, governance, access to authority, responsibility, information sharing, and resource accessibility. The research also discloses that the HIV/AIDS prevention program in DKI Jakarta uses a formal communication mechanism through official letters and an informal one through WhatsApp groups. KPAP DKI Jakarta is responsible for providing sufficient resources, such as financial, technical, and human resources, to support the HIV/AIDS prevention program. The research suggests that enhancing these factors is essential to improve the effectiveness of collaborative governance in the HIV/AIDS prevention program in DKI Jakarta.